Cervical cancer screening in pregnancy at the maternity clinics of Nabil Choucair health center and the Institute of Social Hygiene of Dakar, Senegal: a study on 67 cases - Gassama, Omar; Niang, Mouhamadou Mansour; Faye Dieme, Marie Edouard; Thiam, Ousmane; Gueye, Mamour; Diarra, Mame; Gueye, Ndiaye; Moreira, Philippe Marc; Diallo, Djibril; Cisse, Mamadou Lamine; Cisse, Cheickh Tidiane; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study aims were to develop the epidemiological profile of patients who received Pap smears during pregnancy, to describe aspects of cytological smears performed in pregnant women and to describe the therapeutic management in case of anomalies in the cervical smear during pregnancy. Methods: This was a prospective, descriptive and analytical study conducted from January 15, 2015 to June 31, 2015 at maternity of Nabil Choucair Health Centre and the Institute of Social Hygiene in Dakar. The Pap smear was performed in all patients who had given their consent to the experience. The parameters studied concerned socio-demographic aspects, gynecological and obstetric background, gestational age at the time of collection, cervico-vaginal smear results, diagnostic and therapeutic management of cytological and histological abnormalities. The data collected on a survey sheet prepared for this purpose were entered and analyzed through the version 3.5.3 of Epi info software. Results: During the study period, 67 pregnant women had received a Pap smear. The epidemiological profile of our patient was a paucipare gestity with an average of 3 with extremes ranging from 1 to 7, an average parity of 2.4 with extremes ranging from 1 to 7. The mean age of pregnancy was 15.4 weeks of amenorrhea (range of 6 and 32 weeks). Only 5 patients (7.4%) had already received a cervical-vaginal swab before the study. The smear was normal in 88.7% of the cases but got abnormalities in 11.3% of the cases. The abnormalities were mainly found in squamous cells and were divided into low-grade lesions (57.1%) and skew-cell abnormalities whose meaning was undetermined (42.1%). Colposcopy was performed in 8 patients. Colposcopy was normal and satisfactory in 4 patients (50%) and identified as atypical grade 1 transformation in 2 patients (25%) and an atypical grade 2 transformation in 2 patients (25%). From a therapeutic point of view, diathermic loop conduction associated with strapping was performed in one patient (12.5%) for severe dysplasia. In postpartum, all dysplastic cervical lesions diagnosed during pregnancy had declined. Conclusions: In the context of our study, where there is no organized screening policy for cervical cancer, antenatal clinics are an excellent screening opportunity to seize.